Peran Iklan #RambutCapek di Instagram dan X dalam Mendorong Minat Beli Konsumen - Agnes Monica Marpaung; Asep Suryana; Gema Nusantara Bakry (Universitas Tarakanita, 2025)
The diversity of shampoo brands demands innovative marketing strategies to highlight their products. The use of male models as the primary representation in Pantene Indonesia shampoo advertisements is a new step that shifts the advertising paradigm, which previously always emphasized the feminist side. This study aims to measure the role of the Pantene Shampoo advertisement